2023
DOI: 10.1161/circulationaha.122.062779
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Apixaban With the Vitamin K Antagonist Phenprocoumon in Patients on Chronic Hemodialysis: The AXADIA-AFNET 8 Study

Abstract: Background: Non-vitamin K oral anticoagulants (NOACs) have become the standard therapy for preventing stroke and ischemic thromboembolism in most patients with atrial fibrillation (AF). The effectiveness and safety of NOACs in patients on hemodialysis is not well known. Methods: From June 2017 until May 2022, the investigator-initiated, prospective, randomized, open, blinded outcome assessment 'A Safety Study Assessing Oral Anticoagulation with ApiXAban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 34 publications
0
69
0
6
Order By: Relevance
“…74 Still, evidence is accruing on the use of direct factor Xa inhibitors in patients with severe chronic kidney disease or on dialysis. 75,76 Two phase 2 randomized trials of IONIS-FXI Rx and xisomab 3G3 have been conducted and completed (Table 4). IONIS-FXI Rx is a promising compound for the ESRD population because of its predictable pharmacokinetics and no evidence of drug accumulation.…”
Section: Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Still, evidence is accruing on the use of direct factor Xa inhibitors in patients with severe chronic kidney disease or on dialysis. 75,76 Two phase 2 randomized trials of IONIS-FXI Rx and xisomab 3G3 have been conducted and completed (Table 4). IONIS-FXI Rx is a promising compound for the ESRD population because of its predictable pharmacokinetics and no evidence of drug accumulation.…”
Section: Patients With Esrdmentioning
confidence: 99%
“…74 Still, evidence is accruing on the use of direct factor Xa inhibitors in patients with severe chronic kidney disease or on dialysis. 75,76…”
Section: Current Investigationsmentioning
confidence: 99%
“…Diese letztere Beobachtung ließ sich einerseits auf eine erhöhte Quote intrakranieller Blutungen und hämorrhagischer Schlaganfälle zurückführen, weist aber andererseits gleichwohl auf den weiter oben schon einmal dargestellten Umstand hin, dass es keinerlei kontrollierte Studiendaten gibt, aufgrund derer eine Reduktion des Schlaganfallrisikos bei Dialysepatient*innen mit Vorhofflimmern durch Antikoagulation als zweifelsfrei gesichert betrachtet werden kann. Die AXADIA-Studie randomisierte schließlich 97 Dialysepatient*innen (Apixaban-Arm mit 2 × 2,5 mg), wobei es im Vergleich der beiden Gruppen zu keinen signifikanten Unterschieden hinsichtlich der Wirksamkeits-und Sicherheitsendpunkte kam, was aber u. U. an "Underpowerment" lag (numerisch Apixaban vs. VKA: Schlaganfälle: 20,8 vs. 30,6 %; Blutungen: 10,4 vs. 12,2 %) [30]. Die RE-NAL-AF-Studie randomisierte 154 Dialysepatient*innen mit Vorhofflimmern zu Apixaban (2 × 5 mg, bzw.…”
Section: Wurden Dann Auch In Einer Pharmakodynamischenunclassified
“…14 Recently, two trials have not reported positive results comparing apixaban versus warfarin for dialysis patients. 15,16 Left atrial appendage occlusion (LAAO) has emerged as a nonpharmacological alternative to prevent thromboembolic events in nonvalvular AF patients. 17,18 Around 90% of left atrial thrombi are located in the left atrium appendage, 19,20 this is even higher in CKD patients, due to its influence on the prothrombotic state.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been demonstrated that benefits from some therapies cannot be extrapolated from non‐CKD to CKD cohorts, such as statins in CKD stage 5 14 . Recently, two trials have not reported positive results comparing apixaban versus warfarin for dialysis patients 15,16 …”
Section: Introductionmentioning
confidence: 99%